Implementation of Teacher's Individual Approach in Improving Students' Learning Outcomes in Islamic Education Subjects - Tasya Lestari Amelia; Andi Anirah; Ahmad Syahid; Erniati (Tadrib: Jurnal Pendidikan Agama Islam, 2026)
The individual approach is becoming increasingly important in the digital era due to the easy accessibility of technology. The availability of this technology is a driving force for a society that demands a more flexible and relevant educational model, one that can be tailored (customized) to the learning style and unique needs of each individual. The objective of this research is to describe the implementation of the individual approach and to determine the effectiveness of this individual approach on improving students' learning outcomes in the subject of Islamic Religious Education (PAI). This research uses a qualitative approach with a descriptive design. The research was conducted at SMP Negeri 7 Palu, Palu City, Central Sulawesi. The main data collection techniques used were observation, interviews, and documentation. The qualitative data analysis is inductive, involving data reduction, data presentation, and data verification. The validity of the data was checked using the triangulation technique. The results of the research show that the implementation of the individual approach by the PAI teacher at SMP Negeri 7 Palu is carried out by motivating students in character building, using the individual approach method to increase concentration and self-confidence, acting as a facilitator and guide, and giving homework to instill discipline and responsibility. Furthermore, regarding the effectiveness of the individual approach on improving students' learning outcomes, the improvement in learning outcomes is achieved through emotional contact by the principal and the PAI teacher to identify student issues, creating a comfortable atmosphere as a facilitator, providing motivation, and implementing positive habits.